The Relationship Between Viral Load Levels and CD4+ Count with the Incidence of Opportunistic Infections in HIV/AIDS Patients at Ibnu Sina Hospital Makassar - Daud, Nur Ramahdani; Vitayani, Sri; Harahap, Muhammad Wirawan; Waspodo, Nurelly Noro; Irmayanti, Irmayanti (Faculty of Medicine, Universitas Tadulako, 2025)
Background: HIV/AIDS is a global health problem that continues to be a challenge, especially in developing countries. One important aspect in the management of HIV/AIDS is the monitoring of viral load and CD4+ levels which serve as indicators of the patient's immune status. As the disease progresses, HIV/AIDS patients are at high risk of opportunistic infections that can worsen health conditions and shorten life expectancy. Objective: To determine the relationship between viral load and CD4+ levels in HIV/AIDS patients at Ibnu Sina Hospital. Method: Analytic observational research method with cross sectional approach, the research subjects were 10 subjects for viral load examination and 32 subjects for CD4+ examination. Results: The highest percentage of opportunistic infections was in oral candidiasis infection as many as 16 people (50%). The chi-square test showed a significant relationship between CD4+ levels and opportunistic infections in HIV/AIDS patients at Ibnu Sina Hospital Makassar with a p-value of 0.000 while for viral load could not be determined because secondary data were incomplete. Conclusion: There is a significant relationship between CD4+ levels with opportunistic infections in patients with HIV/AIDS at Ibnu Sina Hospital Makassar.